Increased symplasmic permeability in barley root epidermal cells correlates with defects in root hair development. (8th August 2013) - Marzec, M.; Muszynska, A.; Melzer, M.; Sas‐Nowosielska, H.; Kurczynska, E. U.; Wick, S.
Abstract It is well known that the process of plant cell differentiation depends on the symplasmic isolation of cells. Before starting the differentiation programme, the individual cell or group of cells should restrict symplasmic communication with neighbouring cells. We tested the symplasmic communication between epidermal cells in the different root zones of parental barley plants Hordeum vulgare L., cv. 'Karat' with normal root hair development, and two root hairless mutants (rhl1.a and rhl1.b). The results clearly show that symplasmic communication was limited during root hair differentiation in the parental variety, whereas in both root hairless mutants epidermal cells were still symplasmically connected in the corresponding root zone. This paper is the first report on the role of symplasmic isolation in barley root cell differentiation, and additionally shows that a disturbance in the restriction of symplasmic communication is present in root hairless mutants.